Low-dielectric-loss aluminum oxide ceramic structural member and preparation method thereof

By using raw materials such as alumina powder and magnesium source compounds, combined with ball milling, centrifugal spray granulation and cold isostatic press forming processes, high-purity and low dielectric loss alumina ceramic structural parts were prepared, which solved the problems of high cost and poor performance in the existing technology, and realized ceramic structural parts that meet the requirements of semiconductor equipment.

CN119797900APending Publication Date: 2025-04-11SUZHOU KEY MATERIALS TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411983677.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

It is difficult to develop alumina ceramic structural component with low cost, low dielectric loss and impurity ions that meet the requirements of semiconductor processing equipment.

Method used

Alumina powder, magnesium source compounds, dispersants, adhesives, lubricants, granulated powder surface modifiers, defoaming agents and plasticizers are used as preparation materials, and low-dielectric loss alumina ceramic structural parts are prepared through ball milling, centrifugal spray granulation and cold isostatic press forming processes.

Benefits of technology

It realizes high purity (over 99.8 wt% of alumina ceramic structural parts, low dielectric loss and excellent mechanical and electrical properties, and meets the high-precision etching requirements of semiconductor equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222078010000141
    Figure BDA0005222078010000141
  • Figure BDA0005222078010000151
    Figure BDA0005222078010000151
  • Figure BDA0005222078010000161
    Figure BDA0005222078010000161
Patent Text Reader

Abstract

The invention belongs to the field of aluminum oxide ceramic structural parts, and particularly relates to a low-dielectric-loss aluminum oxide ceramic structural part and a preparation method thereof. The low-dielectric-loss aluminum oxide ceramic structural part is prepared from the following raw materials in parts by mass: 100 parts of aluminum oxide powder, 0.1 to 0.3 part of a sintering aid, 2 to 4 parts of a dispersing agent, 3 to 2 parts of an adhesive, 0.8 to 2.5 parts of a lubricating agent, 0.2 to 0.4 part of a granulation powder surface modifier, 0.01 to 0.05 part of a defoaming agent and 0.5 to 1 part of a plasticizer modifier, a defoaming agent and a plasticizer. Wherein the sintering aid is a magnesium source compound, and the magnesium element content in the magnesium source compound is 500-1200 ppm of the mass of the aluminum oxide powder. The aluminum oxide ceramic structural member prepared by the method has relatively high density, has relatively low dielectric loss in a MHz frequency band, and is particularly suitable for being used by nanoscale chip production equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of alumina ceramic structural parts, and specifically relates to a low dielectric loss alumina ceramic structural part and a preparation method thereof. Background Art

[0002] In the semiconductor industry, manufacturing nanoscale chips often requires complex and expensive production equipment. Compared with expanding production capacity, chip manufacturers prefer to improve the processing accuracy and yield of equipment. For operating plasma etching equipment, the uneven electrical properties of the edge area of ​​the wafer will cause the plasma sheath to deform in this area, thereby shifting the plasma motion trajectory at the edge of the wafer, ultimately affecting the etching accuracy. To solve this problem, the low dielectric loss alumina ceramic structural parts used in the chamber can effectively improve the continuity of the electrical properties of the plasma at the edge of the wafer, reduce plasma distortion, and thus enhance the etching accuracy of the equipment. In addition, alumina ceramic structural parts must also meet the basic requirements of semiconductor equipment for high purity, stable performance, and precise dimensions.

[0003] The dielectric loss of materials mainly comes from two aspects: intrinsic loss and non-intrinsic loss. Intrinsic loss is closely related to the crystal structure, reflecting the interaction between the lattice and the external electric field; while non-intrinsic loss is related to the microstructure of the material such as microscopic defects, porosity, microcracks and impurities. At present, the common method for preparing low dielectric loss alumina is through element doping, such as single or multiple elements such as titanium, magnesium, yttrium, and lanthanum. For example, patent document CN201710192403.4 reported that trace CaTiO3 doping can effectively reduce the dielectric loss of alumina ceramics, but the addition of Ti elements may reduce the resistivity of the material, resulting in uneven charge distribution around the ceramic components in the plasma etching chamber, thereby affecting the plasma etching trajectory and reducing the etching accuracy. Patent document CN201810993942.2 discloses a ternary doping formula of MgO, ZrO2, and Y2O3 to control the grain size of alumina ceramic substrates. However, the solubility of these doping elements in alumina is limited, and the dielectric loss of ZrO2 is relatively high, making it difficult to effectively suppress the dielectric loss of ceramic parts. Zhang Juxian's team from the 12th Institute of China Electronics Technology Group Corporation used 3N alumina powder with a particle size of less than 0.4μm, and prepared alumina materials with low dielectric loss in the GHz frequency band through single-phase magnesium oxide doping and two-step sintering technology. However, overly fine alumina powder is easy to agglomerate during mixing and molding, and ceramics sintered under low sintering aid conditions are prone to microscopic defects, which reduces the material density while increasing the dielectric loss; and although the process flow of the two-step atmosphere sintering method increases the density, it also increases the production cost of the material.

[0004] Therefore, developing a low-cost, low-dielectric-loss alumina ceramic structural component whose impurity ions meet the requirements of semiconductor processing equipment is one of the industry-wide technical challenges that the semiconductor support industry urgently needs to solve. Summary of the invention

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a low dielectric loss alumina ceramic structural component, the preparation raw materials of which include: alumina powder, sintering aid, dispersant, adhesive, lubricant, granulation powder surface modifier, defoamer and plasticizer.

[0006] As an implementable case, the raw materials for preparing the alumina ceramic structural parts include, by mass, 100 parts of alumina powder, 0.1-0.3 parts of sintering aid, 2-4 parts of dispersant, 3-2 parts of adhesive, 0.8-2.5 parts of lubricant, 0.2-0.4 parts of granulation powder surface modifier, 0.01-0.05 parts of defoaming agent, and 0.5-1 parts of plasticizer.

[0007] As an implementable case, the purity of the aluminum oxide powder is greater than 99.99wt%, and the average particle size is less than 1.5μm.

[0008] Furthermore, the alumina powder includes: alumina powder with a brand name of AHP300 (average particle size of 1-1.4 μm, produced by Japan Light Metal, purchased by Dalian Guomao Materials Technology Co., Ltd., with a purity greater than 99.99wt%).

[0009] If the purity of alumina powder is too low, the impurity ion content will increase, which will not only increase dielectric loss and affect the electrical properties of the material, but also contaminate the wafer during the etching process, reducing product quality. At the same time, the appropriate particle size selection also has a significant impact on the performance of ceramics. Too fine alumina powder may cause more internal defects in ceramic components due to easy agglomeration, while too coarse powder is difficult to form a dense microstructure due to insufficient sintering activity, affecting the overall strength and dielectric properties of the ceramic.

[0010] As an implementable case, the sintering aid is a magnesium source compound.

[0011] As an implementable case, the magnesium source compound includes: magnesium oxide (available from Shanghai McLean Biochemical Technology Co., Ltd., CAS: 1309-48-4, purity 99%, item number: M813080, average particle size <50nm), magnesium hydroxide (available from Shanghai McLean Biochemical Technology Co., Ltd., CAS: 1309-42-8, purity ≥99wt%, item number: M799580), magnesium nitrate hexahydrate, and one or more of magnesium carbonate.

[0012] Furthermore, the magnesium content in the magnesium source compound is 500-1200 ppm (1 ppm = 1×10 -6 ).

[0013] During the sintering process, magnesium source compounds, as sintering aids, can activate the lattice, increase the sintering activity of alumina, accelerate the gas discharge during the sintering process, significantly improve the density and strength of the material, and then enhance the mechanical properties (such as hardness, wear resistance) and electrical properties (such as dielectric constant, resistivity) of ceramic structural parts, ensuring that they can work stably in radio frequency electric fields and corrosion environments, and meet the requirements of high-precision etching. At the same time, magnesium source compounds can also inhibit abnormal grain growth, optimize the microstructure, and greatly improve the mechanical and electrical properties of ceramic structural parts and reduce dielectric loss by refining grains and improving grain uniformity.

[0014] The present invention further defines the magnesium content in the magnesium source compound as 500-1200ppm of the mass of the alumina powder. When the magnesium element is added too much, the magnesium source compound can form a second phase or impurity in the ceramic, becoming a trap for charge carriers and increasing dielectric loss; at the same time, excessive magnesium will cause the ceramic to shrink too fast during sintering, forming pores that are difficult to remove. The pores will cause the movement and redistribution of charges under the action of the electric field, further increasing the dielectric loss. On the contrary, adding too little magnesium will cause the sintering activity of the alumina material to be insufficient. The insufficient activity generally requires increasing the sintering temperature to compensate, but the high sintering temperature can easily lead to abnormal growth of the grain size and uneven local sintering speed, and gaps and holes between particles that are not tightly bonded are likely to appear inside the material. These abnormally grown grains and microscopic defects reduce the mechanical properties of the material on the one hand, limit the application environment of the material, and on the other hand also increase the non-intrinsic loss of the material.

[0015] As an implementable case, the dispersant includes: sorbitan monooleate (available from Jiangsu Hai'an Petrochemical, brand: S-80, purity 98.5wt%), ammonium polyacrylate (available from Hubei Jusheng Technology Co., Ltd., item number: JS2658, purity ≥99wt%), ammonium polycarboxylate (available from Jining Tangyi Chemical Co., Ltd., item number: SN-5027), polyvinyl pyrrolidone (available from Guangdong Yuemei Chemical Co., Ltd., item number: K30), and one or more of ethylenediaminetetraacetic acid ammonium salt.

[0016] Dispersants can ensure that alumina powder and sintering aids are evenly dispersed in the dispersion medium for a long time, reduce particle agglomeration and sedimentation, improve the stability of ceramic slurry, and ensure that the granulated powder has a uniform microstructure and good forming properties during the spray granulation process, thereby reducing microscopic defects in the final ceramic structural parts.

[0017] As an implementable case, the adhesive includes: PVA (available from Guangzhou Qihua New Material Technology Co., Ltd., degree of polymerization: 550-650, brand: 205PVA, solid content 30wt%), methyl methacrylate, and one or more of maltodextrin.

[0018] The adhesive can penetrate into the gaps between ceramic particles and tightly combine with the ceramic particles through physical adsorption and capillary action, which can increase the contact area and friction between the particles, thereby improving the strength of the green body.

[0019] As an implementable case, the lubricant includes: stearic acid (available from Guangzhou Fangli New Material Technology Co., Ltd., brand: WFL-X33, content 35wt%), oxidized polyethylene wax emulsion (available from Guangzhou Aoyate Chemical Factory, brand: 1502C, content ≥35wt%), and one or more of triglycerides.

[0020] During the cold isostatic pressing process, alumina powder particles need to be uniformly compressed to form a dense green body. However, the friction between powder particles will interfere with the uniform transmission of pressure, thereby causing stress concentration and defects inside the green body. Lubricants can effectively reduce the friction coefficient between particles, ensuring that pressure can act more evenly on each particle, thereby significantly reducing the formation of green body defects. In addition, alumina ceramic powder particles may bond due to mutual contact during the cold isostatic pressing process to form agglomerates, which will affect the density and uniformity of the green body. Lubricants can form a lubricating film between particles, effectively preventing direct contact and bonding of particles, and maintaining good dispersion of the powder.

[0021] As an implementable case, the granulation powder surface modifier includes: cationic polyacrylamide (available from Shanghai McLean Biochemical Technology Co., Ltd., product number: P875616, degree of polymerization: 8 million to 10 million, purity ≥90wt%), hydroxypropyl methylcellulose (available from Shandong Weifang Lite Composite Materials Co., Ltd., brand: HT-F, purity ≥95wt%), and one or more of ethyl cellulose.

[0022] During the cold isostatic pressing process, the uniformity and dispersibility of alumina granulation powder have a certain influence on the density and mechanical properties of ceramic structural parts. If the powder has poor fluidity, it is easy to form dead corners and voids when filling the mold, resulting in internal defects such as pores and cracks. The surface modifier of granulation powder can change the physical and chemical properties of the particle surface (such as reducing surface energy, increasing sliding properties, and improving the sphericity of granulation powder), significantly improve the powder fluidity, make the powder easier to distribute evenly in the mold, and reduce defects. At the same time, the surface modifier of granulation powder can also reduce friction and adhesion between particles, prevent the formation of agglomerates, further reduce the defects of the vibrated filler before cold isostatic pressing, and improve the stability of ceramic structural parts.

[0023] As an implementable case, the defoaming agent includes: fatty alcohol polyoxyethylene ether (available from Shandong Yunxin New Material Technology Co., Ltd., brand: AEO-3), acetylene glycol (available from Yingde Chuangzhi New Material Technology Co., Ltd.), glycerol polyoxypropylene ether (available from Jiangsu Hai'an Petrochemical Plant, brand: GP330), and one or more of isopropanol.

[0024] Defoaming agents can effectively destroy the surface tension of foam in alumina slurry, causing the foam to disappear quickly and inhibiting the generation of new foam for a long time.

[0025] As an implementable case, the plasticizer includes: PEG (available from Guangzhou Jinglong Technology Co., Ltd., purity ≥99wt%, brand: PEG-4000 or PEG-8000), dibutyl phthalate (available from Yancheng Xinjinyuan Oil Technology Co., Ltd., content ≥99.5%), and one or more of diethylene glycol acetate.

[0026] The plasticity of alumina powder can be significantly enhanced after adding plasticizer, making the powder easier to compress and shape during molding, improving the processing performance of the green body after molding, and thus being able to produce ceramic structural parts with more complex shapes and higher precision.

[0027] A second aspect of the present invention provides a method for preparing a low dielectric loss alumina ceramic structural component, comprising:

[0028] S1. Add sintering aid, dispersant, adhesive, lubricant, granulation powder surface modifier, defoamer and plasticizer into the ball mill containing grinding media and mix them evenly;

[0029] S2, adding alumina powder, ball milling for 8-24 hours, and then centrifugal spray granulation to obtain granulated powder;

[0030] S3. Fill the mold with granulated powder, seal it, and cold isostatically press it at 180-220 MPa for 10-20 min to obtain a green body. Then, air sinter it at 1590-1640°C for 2-4 h to obtain the green body.

[0031] As an implementable example, the grinding media are aluminum oxide grinding media and water.

[0032] Furthermore, the mass ratio of the alumina grinding medium, water and alumina powder is 8:1:2.

[0033] Beneficial Effects

[0034] (I) The low dielectric loss alumina prepared by the present invention has a purity of more than 99.8 wt %, and uses a magnesium source compound as a single inorganic sintering aid, which meets the strict requirements of semiconductor equipment on the type and purity of impurity ions.

[0035] (ii) In the process of preparing low dielectric loss ceramic structural parts, the present invention adds lubricants in the slurrying stage. One end of the lubricant is anchored on the particle surface, and the other end constructs a lubricating layer on the powder surface, which significantly reduces the sliding friction coefficient between particles and reduces the resistance during relative sliding. Therefore, when the material is pressurized and formed, the powder particles can move more smoothly and fill the gaps, thereby increasing the green density and effectively reducing the microscopic defects of the ceramic.

[0036] (III) The present invention also introduces a granulation powder surface modifier to optimize the surface morphology of the granulation powder, significantly improving its fluidity and uniformity during the powder filling process, as well as the filling density, which is beneficial to further reduce the microscopic defects of the ceramic.

[0037] (IV) The average particle size of the alumina powder used in the present invention is limited to the range of 1 to 1.4 μm. While ensuring the sintering activity, it effectively prevents the agglomeration of the ceramic slurry, improves the uniformity of the slurry, and improves the density of the green body after molding, thereby promoting the improvement of the ceramic density. Compared with the work of Zhang Juxian's team, the present invention avoids the step of secondary sintering and still achieves an increase in product density.

[0038] (V) The present invention specifically limits the content range of magnesium element in the magnesium source compound, i.e., 500 to 1200 ppm of the mass of the alumina powder, thereby ensuring that the ceramic structural parts have lower dielectric loss and better material density. The density of the product is ≥3.94 g / cc, and the dielectric loss at 13.56 MHz is <0.0005. DETAILED DESCRIPTION

[0039] Example 1

[0040] The first aspect of this example provides a low dielectric loss alumina ceramic structural component, the raw materials for its preparation are, by weight, specifically: 5kg alumina powder, 5g magnesium oxide, 140g sorbitan monooleate, 170g PVA, 45g oxidized polyethylene wax emulsion, 12g cationic polyacrylamide, 3g glycerol polyoxypropylene ether, and 30g PEG.

[0041] The aluminum oxide powder is of AHP300 with an average particle size of 1 to 1.4 μm. It is produced by Japan Light Metal and purchased by Dalian Guomao Materials Technology Co., Ltd. with a purity greater than 99.99 wt%.

[0042] The magnesium oxide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS: 1309-48-4, purity 99%, item number: M813080, average particle size <50 nm.

[0043] The sorbitan monooleate was purchased from Jiangsu Haian Petrochemical, with the brand name S-80 and a purity of 98.5 wt %, and was diluted with water to a solid content of 40 wt %.

[0044] The PVA was purchased from Guangzhou Qihua New Material Technology Co., Ltd., with a polymerization degree of 550-650, a brand name: 205PVA, and a solid content of 30wt%.

[0045] The oxidized polyethylene wax emulsion was purchased from Guangzhou Aoyate Chemical Factory, with the brand name: 1502C and a content of ≥35wt%.

[0046] The cationic polyacrylamide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with the item number P875616, molecular weight of 8 million to 10 million, and purity ≥ 90 wt %; it was diluted with water to a solid content of 25 wt %.

[0047] The glycerol polyoxypropylene ether was purchased from Haian Petrochemical Plant in Jiangsu Province, with the brand name: GP330.

[0048] The PEG was purchased from Guangzhou Jinglong Technology Co., Ltd., with a purity of ≥99wt%, and a brand name of PEG-4000.

[0049] The second aspect of this example provides a method for preparing a low dielectric loss alumina ceramic structural component, comprising:

[0050] S1. Add magnesium oxide, sorbitan monooleate, PVA, oxidized polyethylene wax emulsion, cationic polyacrylamide, glycerol polyoxypropylene ether and PEG into a ball mill containing grinding media (20 kg alumina grinding media and 2.5 kg water), and mix well.

[0051] S2, adding alumina powder, ball milling for 8 hours, and then centrifugal spray granulation to obtain granulated powder with an average particle size of 45-60 μm;

[0052] S3. The granulated powder is loaded into the mold, which is then sealed and cold isostatically pressed at 180 MPa for 20 min to obtain a green body. The green body is then sintered in air at 1590°C and 1 atm for 3 h.

[0053] Example 2

[0054] The first aspect of this example provides a low dielectric loss alumina ceramic structural component, the raw materials for its preparation are, by weight, specifically: 5kg alumina powder, 9g magnesium oxide, 180g sorbitan monooleate, 230g PVA, 65g oxidized polyethylene wax emulsion, 18g cationic polyacrylamide, 5g glycerol polyoxypropylene ether, and 40g PEG.

[0055] The aluminum oxide powder is of AHP300 with an average particle size of 1 to 1.4 μm. It is produced by Japan Light Metal and purchased by Dalian Guomao Materials Technology Co., Ltd. with a purity greater than 99.99 wt%.

[0056] The magnesium oxide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS: 1309-48-4, purity 99%, item number: M813080, average particle size <50 nm.

[0057] The sorbitan monooleate was purchased from Jiangsu Haian Petrochemical, with the brand name S-80 and a purity of 98.5 wt %, and was diluted with water to a solid content of 40 wt %.

[0058] The PVA was purchased from Guangzhou Qihua New Material Technology Co., Ltd., with a polymerization degree of 550-650, a brand name: 205PVA, and a solid content of 30wt%.

[0059] The oxidized polyethylene wax emulsion was purchased from Guangzhou Aoyate Chemical Factory, with the brand name: 1502C and a content of ≥35wt%.

[0060] The cationic polyacrylamide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with the item number P875616, molecular weight of 8 million to 10 million, and purity ≥ 90 wt %; it was diluted with water to a solid content of 25 wt %.

[0061] The glycerol polyoxypropylene ether was purchased from Haian Petrochemical Plant in Jiangsu Province, with the brand name: GP330.

[0062] The PEG was purchased from Guangzhou Jinglong Technology Co., Ltd., with a purity of ≥99wt%, and a brand name of PEG-4000.

[0063] The second aspect of this example provides a method for preparing a low dielectric loss alumina ceramic structural component, comprising:

[0064] S1. Add magnesium oxide, sorbitan monooleate, PVA, oxidized polyethylene wax emulsion, cationic polyacrylamide, glycerol polyoxypropylene ether and PEG into a ball mill containing grinding media (20 kg alumina grinding media and 2.5 kg water), and mix well.

[0065] S2, adding alumina powder, ball milling for 8 hours, and then centrifugal spray granulation to obtain granulated powder with an average particle size of 45-60 μm;

[0066] S3. The granulated powder is loaded into the mold, which is then sealed and cold isostatically pressed at 220 MPa for 20 min to obtain a green body. The green body is then sintered in air at 1640°C and 1 atm for 3 h.

[0067] Example 3

[0068] The first aspect of this example provides a low dielectric loss alumina ceramic structural component, the raw materials for its preparation are, by weight, specifically: 5 kg alumina powder, 13 g magnesium hydroxide, 160 g ammonium polycarboxylate, 200 g PVA, 50 g stearic acid emulsion, 18 g hydroxypropyl methylcellulose, 4 g fatty alcohol polyoxyethylene ether, and 40 g dibutyl phthalate.

[0069] The aluminum oxide powder is of AHP300 with an average particle size of 1 to 1.4 μm. It is produced by Japan Light Metal and purchased by Dalian Guomao Materials Technology Co., Ltd. with a purity greater than 99.99 wt%.

[0070] The magnesium hydroxide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS: 1309-42-8, purity ≥ 99wt%, item number: M799580.

[0071] The ammonium polycarboxylate was purchased from Jining Tangyi Chemical Co., Ltd., with the brand name SN-5027.

[0072] The PVA was purchased from Guangzhou Qihua New Material Technology Co., Ltd., with a polymerization degree of 550-650, a brand name: 205PVA, and a solid content of 30wt%.

[0073] The stearic acid emulsion was purchased from Guangzhou Fangli New Material Technology Co., Ltd., brand: WFL-X33, content 35wt%.

[0074] The hydroxypropyl methylcellulose was purchased from Shandong Weifang Lite Composite Materials Co., Ltd., brand: HT-F, purity ≥ 95wt%, and diluted with water to a solid content of 25wt%.

[0075] The fatty alcohol polyoxyethylene ether was purchased from Shandong Yunxin New Material Technology Co., Ltd., brand: AEO-3.

[0076] The dibutyl phthalate was purchased from Yancheng Xinjinyuan Oil Technology Co., Ltd., with a content of ≥99.5%.

[0077] The second aspect of this example provides a method for preparing a low dielectric loss alumina ceramic structural component, comprising:

[0078] S1. Add magnesium hydroxide, ammonium polycarboxylate, PVA, stearic acid emulsion, hydroxypropyl methylcellulose, fatty alcohol polyoxyethylene ether and dibutyl phthalate into a ball mill containing grinding media (20 kg alumina grinding media and 2.5 kg water), and mix well.

[0079] S2, adding alumina powder, ball milling for 8 hours, and then centrifugal spray granulation to obtain granulated powder with an average particle size of 45-60 μm;

[0080] S3. The granulated powder is loaded into the mold, which is then sealed and cold isostatically pressed at 220 MPa for 20 min to obtain a green body. The green body is then sintered in air at 1620°C and 1 atm for 4 h.

[0081] Comparative Example 1

[0082] The first aspect of this example provides a low dielectric loss alumina ceramic structural component, the raw materials for its preparation are, by weight, specifically: 5kg alumina powder, 9g magnesium oxide, 140g sorbitan monooleate, 190g PVA, 60g oxidized polyethylene wax emulsion, 18g cationic polyacrylamide, 5g glycerol polyoxypropylene ether, and 40g PEG.

[0083] The aluminum oxide powder is SAO-030E-N, has an average particle size of less than 0.6 μm, is purchased from Shandong Guoci Functional Materials Co., Ltd., and has a purity of more than 99.9 wt%.

[0084] The magnesium oxide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS: 1309-48-4, purity 99%, item number: M813080, average particle size <50 nm.

[0085] The sorbitan monooleate was purchased from Jiangsu Haian Petrochemical, with the brand name S-80 and a purity of 98.5 wt %, and was diluted with water to a solid content of 40 wt %.

[0086] The PVA was purchased from Guangzhou Qihua New Material Technology Co., Ltd., with a polymerization degree of 550-650, a brand name: 205PVA, and a solid content of 30wt%.

[0087] The oxidized polyethylene wax emulsion was purchased from Guangzhou Aoyate Chemical Factory, with the brand name: 1502C and a content of ≥35wt%.

[0088] The cationic polyacrylamide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with the item number P875616, molecular weight of 8 million to 10 million, and purity ≥ 90 wt %; it was diluted with water to a solid content of 25 wt %.

[0089] The glycerol polyoxypropylene ether was purchased from Haian Petrochemical Plant in Jiangsu Province, with the brand name: GP330.

[0090] The PEG was purchased from Guangzhou Jinglong Technology Co., Ltd., with a purity of ≥99wt%, and a brand name of PEG-8000.

[0091] The second aspect of this example provides a method for preparing a low dielectric loss alumina ceramic structural component, comprising:

[0092] S1. Add magnesium oxide, sorbitan monooleate, PVA, oxidized polyethylene wax emulsion, cationic polyacrylamide, glycerol polyoxypropylene ether and PEG into a ball mill containing grinding media (20 kg alumina grinding media and 2.5 kg water), and mix well.

[0093] S2, adding alumina powder, ball milling for 8 hours, and then centrifugal spray granulation to obtain granulated powder with an average particle size of 45-60 μm;

[0094] S3. The granulated powder is loaded into the mold, which is then sealed and cold isostatically pressed at 220 MPa for 20 min to obtain a green body. The green body is then sintered in air at 1610°C and 1 atm for 3 h.

[0095] Comparative Example 2

[0096] The first aspect of this example provides a low dielectric loss alumina ceramic structural component, the raw materials for its preparation are, by weight, specifically: 5kg alumina powder, 9g magnesium oxide, 160g sorbitan monooleate, 190g PVA, 30g oxidized polyethylene wax emulsion, 8g cationic polyacrylamide, 5g glycerol polyoxypropylene ether, and 40g PEG.

[0097] The aluminum oxide powder is of AHP300 with an average particle size of 1 to 1.4 μm. It is produced by Japan Light Metal and purchased by Dalian Guomao Materials Technology Co., Ltd. with a purity greater than 99.99 wt%.

[0098] The magnesium oxide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS: 1309-48-4, purity 99%, item number: M813080, average particle size <50 nm.

[0099] The sorbitan monooleate was purchased from Jiangsu Haian Petrochemical, with the brand name S-80 and a purity of 98.5 wt %, and was diluted with water to a solid content of 40 wt %.

[0100] The PVA was purchased from Guangzhou Qihua New Material Technology Co., Ltd., with a polymerization degree of 550-650, a brand name: 205PVA, and a solid content of 30wt%.

[0101] The oxidized polyethylene wax emulsion was purchased from Guangzhou Aoyate Chemical Factory, with the brand name: 1502C and a content of ≥35wt%.

[0102] The cationic polyacrylamide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with the item number P875616, molecular weight of 8 million to 10 million, and purity ≥ 90 wt %; it was diluted with water to a solid content of 25 wt %.

[0103] The glycerol polyoxypropylene ether was purchased from Haian Petrochemical Plant in Jiangsu Province, with the brand name: GP330.

[0104] The PEG was purchased from Guangzhou Jinglong Technology Co., Ltd., with a purity of ≥99wt%, and a brand name of PEG-4000.

[0105] The second aspect of this example provides a method for preparing a low dielectric loss alumina ceramic structural component, comprising:

[0106] S1. Add magnesium oxide, sorbitan monooleate, PVA, oxidized polyethylene wax emulsion, cationic polyacrylamide, glycerol polyoxypropylene ether and PEG into a ball mill containing grinding media (20 kg alumina grinding media and 2.5 kg water), and mix well.

[0107] S2, adding alumina powder, ball milling for 8 hours, and then centrifugal spray granulation to obtain granulated powder with an average particle size of 45-60 μm;

[0108] S3. The granulated powder is loaded into the mold, which is then sealed and cold isostatically pressed at 220 MPa for 20 min to obtain a green body. The green body is then sintered in air at 1620°C and 1 atm for 3 h.

[0109] Comparative Example 3

[0110] The first aspect of this example provides a low dielectric loss alumina ceramic structural component, the raw materials for its preparation are, by weight, specifically: 5kg alumina powder, 9g magnesium oxide, 160g sorbitan monooleate, 190g PVA, 60g oxidized polyethylene wax emulsion, 16g cationic polyacrylamide, 5g glycerol polyoxypropylene ether, and 40g PEG.

[0111] The aluminum oxide powder is of AHP300 with an average particle size of 1 to 1.4 μm. It is produced by Japan Light Metal and purchased by Dalian Guomao Materials Technology Co., Ltd. with a purity greater than 99.99 wt%.

[0112] The magnesium oxide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS: 1309-48-4, purity 99%, item number: M813080, average particle size <50 nm.

[0113] The sorbitan monooleate was purchased from Jiangsu Haian Petrochemical, with the brand name S-80 and a purity of 98.5 wt %, and was diluted with water to a solid content of 40 wt %.

[0114] The PVA was purchased from Guangzhou Qihua New Material Technology Co., Ltd., with a polymerization degree of 550-650, a brand name: 205PVA, and a solid content of 30wt%.

[0115] The oxidized polyethylene wax emulsion was purchased from Guangzhou Aoyate Chemical Factory, with the brand name: 1502C and a content of ≥35wt%.

[0116] The cationic polyacrylamide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with the item number P875616, molecular weight of 8 million to 10 million, and purity ≥ 90 wt %; it was diluted with water to a solid content of 25 wt %.

[0117] The glycerol polyoxypropylene ether was purchased from Haian Petrochemical Plant in Jiangsu Province, with the brand name: GP330.

[0118] The PEG was purchased from Guangzhou Jinglong Technology Co., Ltd., with a purity of ≥99wt%, and a brand name of PEG-4000.

[0119] The second aspect of this example provides a method for preparing a low dielectric loss alumina ceramic structural component, comprising:

[0120] S1. Add magnesium oxide, sorbitan monooleate, PVA, oxidized polyethylene wax emulsion, cationic polyacrylamide, glycerol polyoxypropylene ether and PEG into a ball mill containing grinding media (20 kg alumina grinding media and 2.5 kg water), and mix well.

[0121] S2, adding alumina powder, ball milling for 8 hours, and then centrifugal spray granulation to obtain granulated powder with an average particle size of 45-60 μm;

[0122] S3. The granulated powder is loaded into the mold, which is then sealed and cold isostatically pressed at 150 MPa for 20 minutes to obtain a green body. The green body is then sintered in air at 1650°C and 1 atm for 3 hours.

[0123] Comparative Example 4

[0124] The first aspect of this example provides a low dielectric loss alumina ceramic structural component, the raw materials for its preparation are, by weight, specifically: 5kg alumina powder, 9g magnesium oxide, 160g sorbitan monooleate, 190g PVA, 140g oxidized polyethylene wax emulsion, 25g cationic polyacrylamide, 5g glycerol polyoxypropylene ether, and 40g PEG.

[0125] The aluminum oxide powder is of AHP300 with an average particle size of 1 to 1.4 μm. It is produced by Japan Light Metal and purchased by Dalian Guomao Materials Technology Co., Ltd. with a purity greater than 99.99 wt%.

[0126] The magnesium oxide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS: 1309-48-4, purity 99%, item number: M813080, average particle size <50 nm.

[0127] The sorbitan monooleate was purchased from Jiangsu Haian Petrochemical, with the brand name S-80 and a purity of 98.5 wt %, and was diluted with water to a solid content of 40 wt %.

[0128] The PVA was purchased from Guangzhou Qihua New Material Technology Co., Ltd., with a polymerization degree of 550-650, a brand name: 205PVA, and a solid content of 30wt%.

[0129] The oxidized polyethylene wax emulsion was purchased from Guangzhou Aoyate Chemical Factory, with the brand name: 1502C and a content of ≥35wt%.

[0130] The cationic polyacrylamide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with the item number P875616, molecular weight of 8 million to 10 million, and purity ≥ 90 wt %; it was diluted with water to a solid content of 25 wt %.

[0131] The glycerol polyoxypropylene ether was purchased from Haian Petrochemical Plant in Jiangsu Province, with the brand name: GP330.

[0132] The PEG was purchased from Guangzhou Jinglong Technology Co., Ltd., with a purity of ≥99wt%, and a brand name of PEG-4000.

[0133] The second aspect of this example provides a method for preparing a low dielectric loss alumina ceramic structural component, comprising:

[0134] S1. Add magnesium oxide, sorbitan monooleate, PVA, oxidized polyethylene wax emulsion, cationic polyacrylamide, glycerol polyoxypropylene ether and PEG into a ball mill containing grinding media (20 kg alumina grinding media and 2.5 kg water), and mix well.

[0135] S2, adding alumina powder, ball milling for 8 hours, and then centrifugal spray granulation to obtain granulated powder with an average particle size of 45-60 μm;

[0136] S3. The granulated powder is loaded into the mold, which is then sealed and cold isostatically pressed at 220 MPa for 20 min to obtain a green body. The green body is then sintered in air at 1640°C and 1 atm for 3 h.

[0137] Comparative Example 5

[0138] The first aspect of this example provides a low dielectric loss alumina ceramic structural component, the raw materials for its preparation are, by weight, specifically: 5kg alumina powder, 5g magnesium oxide, 220g sorbitan monooleate, 190g PVA, 65g oxidized polyethylene wax emulsion, 8g cationic polyacrylamide, 5g glycerol polyoxypropylene ether, and 30g PEG.

[0139] The aluminum oxide powder is of AHP300 with an average particle size of 1 to 1.4 μm. It is produced by Japan Light Metal and purchased by Dalian Guomao Materials Technology Co., Ltd. with a purity greater than 99.99 wt%.

[0140] The magnesium oxide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS: 1309-48-4, purity 99%, item number: M813080, average particle size <50 nm.

[0141] The sorbitan monooleate was purchased from Jiangsu Haian Petrochemical, with the brand name S-80 and a purity of 98.5 wt %, and was diluted with water to a solid content of 40 wt %.

[0142] The PVA was purchased from Guangzhou Qihua New Material Technology Co., Ltd., with a polymerization degree of 550-650, a brand name: 205PVA, and a solid content of 30wt%.

[0143] The oxidized polyethylene wax emulsion was purchased from Guangzhou Aoyate Chemical Factory, with the brand name: 1502C and a content of ≥35wt%.

[0144] The cationic polyacrylamide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with the item number P875616, molecular weight of 8 million to 10 million, and purity ≥ 90 wt %; it was diluted with water to a solid content of 25 wt %.

[0145] The glycerol polyoxypropylene ether was purchased from Haian Petrochemical Plant in Jiangsu Province, with the brand name: GP330.

[0146] The PEG was purchased from Guangzhou Jinglong Technology Co., Ltd., with a purity of ≥99wt%, and a brand name of PEG-4000.

[0147] The second aspect of this example provides a method for preparing a low dielectric loss alumina ceramic structural component, comprising:

[0148] S1. Add magnesium oxide, sorbitan monooleate, PVA, oxidized polyethylene wax emulsion, cationic polyacrylamide, glycerol polyoxypropylene ether and PEG into a ball mill containing grinding media (20 kg alumina grinding media and 2.5 kg water), and mix well.

[0149] S2, adding alumina powder, ball milling for 8 hours, and then centrifugal spray granulation to obtain granulated powder with an average particle size of 45-60 μm;

[0150] S3. The granulated powder is loaded into the mold, which is then sealed and cold isostatically pressed at 220 MPa for 20 min to obtain a green body. The green body is then sintered in air at 1620°C and 1 atm for 3 h.

[0151] Comparative Example 6

[0152] The first aspect of this example provides a low dielectric loss alumina ceramic structural component, the raw materials for its preparation are, by weight, specifically: 5kg alumina powder, 12g magnesium oxide, 160g sorbitan monooleate, 190g PVA, 65g oxidized polyethylene wax emulsion, 16g cationic polyacrylamide, 5g glycerol polyoxypropylene ether, and 30g PEG.

[0153] The aluminum oxide powder is of AHP300 with an average particle size of 1 to 1.4 μm. It is produced by Japan Light Metal and purchased by Dalian Guomao Materials Technology Co., Ltd. with a purity greater than 99.99 wt%.

[0154] The magnesium oxide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS: 1309-48-4, purity 99%, item number: M813080, average particle size <50 nm.

[0155] The sorbitan monooleate was purchased from Jiangsu Haian Petrochemical, with the brand name S-80 and a purity of 98.5 wt %, and was diluted with water to a solid content of 40 wt %.

[0156] The PVA was purchased from Guangzhou Qihua New Material Technology Co., Ltd., with a polymerization degree of 550-650, a brand name: 205PVA, and a solid content of 30wt%.

[0157] The oxidized polyethylene wax emulsion was purchased from Guangzhou Aoyate Chemical Factory, with the brand name: 1502C and a content of ≥35wt%.

[0158] The cationic polyacrylamide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with the item number P875616, molecular weight of 8 million to 10 million, and purity ≥ 90 wt %; it was diluted with water to a solid content of 25 wt %.

[0159] The glycerol polyoxypropylene ether was purchased from Haian Petrochemical Plant in Jiangsu Province, with the brand name: GP330.

[0160] The PEG was purchased from Guangzhou Jinglong Technology Co., Ltd., with a purity of ≥99wt%, and a brand name of PEG-4000.

[0161] The second aspect of this example provides a method for preparing a low dielectric loss alumina ceramic structural component, comprising:

[0162] S1. Add magnesium oxide, sorbitan monooleate, PVA, oxidized polyethylene wax emulsion, cationic polyacrylamide, glycerol polyoxypropylene ether and PEG into a ball mill containing grinding media (20 kg alumina grinding media and 2.5 kg water), and mix well.

[0163] S2, adding alumina powder, ball milling for 8 hours, and then centrifugal spray granulation to obtain granulated powder with an average particle size of 45-60 μm;

[0164] S3. The granulated powder is loaded into the mold, which is then sealed and cold isostatically pressed at 180 MPa for 20 min to obtain a green body. The green body is then sintered in air at 1570°C and 1 atm for 3 h.

[0165] Comparative Example 7

[0166] The first aspect of this example provides a low dielectric loss alumina ceramic structural component, the raw materials for its preparation are, by weight, specifically: 5kg alumina powder, 3g magnesium oxide, 160g sorbitan monooleate, 190g PVA, 65g oxidized polyethylene wax emulsion, 16g cationic polyacrylamide, 5g glycerol polyoxypropylene ether, and 40g PEG.

[0167] The aluminum oxide powder is of AHP300 with an average particle size of 1 to 1.4 μm. It is produced by Japan Light Metal and purchased by Dalian Guomao Materials Technology Co., Ltd. with a purity greater than 99.99 wt%.

[0168] The magnesium oxide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS: 1309-48-4, purity 99%, item number: M813080, average particle size <50 nm.

[0169] The sorbitan monooleate was purchased from Jiangsu Haian Petrochemical, with the brand name S-80 and a purity of 98.5 wt %, and was diluted with water to a solid content of 40 wt %.

[0170] The PVA was purchased from Guangzhou Qihua New Material Technology Co., Ltd., with a polymerization degree of 550-650, a brand name: 205PVA, and a solid content of 30wt%.

[0171] The oxidized polyethylene wax emulsion was purchased from Guangzhou Aoyate Chemical Factory, with the brand name: 1502C and a content of ≥35wt%.

[0172] The cationic polyacrylamide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with the item number P875616, molecular weight of 8 million to 10 million, and purity ≥ 90 wt %; it was diluted with water to a solid content of 25 wt %.

[0173] The glycerol polyoxypropylene ether was purchased from Haian Petrochemical Plant in Jiangsu Province, with the brand name: GP330.

[0174] The PEG was purchased from Guangzhou Jinglong Technology Co., Ltd., with a purity of ≥99wt%, and a brand name of PEG-4000.

[0175] The second aspect of this example provides a method for preparing a low dielectric loss alumina ceramic structural component, comprising:

[0176] S1. Add magnesium oxide, sorbitan monooleate, PVA, oxidized polyethylene wax emulsion, cationic polyacrylamide, glycerol polyoxypropylene ether and PEG into a ball mill containing grinding media (20 kg alumina grinding media and 2.5 kg water), and mix well.

[0177] S2, adding alumina powder, ball milling for 8 hours, and then centrifugal spray granulation to obtain granulated powder with an average particle size of 45-60 μm;

[0178] S3. The granulated powder is loaded into the mold, which is then sealed and cold isostatically pressed at 180 MPa for 20 min to obtain a green body. The green body is then sintered in air at 1660°C and 1 atm for 3 h.

[0179] The selection of raw material components and the amount of materials used in Examples 1-3 and Comparative Examples 1-7, and the key process parameters are shown in Table 1.

[0180] Table 1

[0181]

[0182]

[0183]

[0184] Performance Evaluation

[0185] Test objects: low dielectric loss alumina ceramic structural parts prepared in Examples 1-3 and Comparative Examples 1-7.

[0186] Test 1. Density test: Test in accordance with GB / T 25995-2010. Weigh the mass of the sample in air, the mass immersed in water and the mass of the wet sample, use a thermometer to test the water temperature to query the corresponding density, and substitute it into the formula to calculate the sample density. The test results are detailed in Table 2.

[0187] Test 2. Dielectric loss test: The test was carried out in accordance with GB / T 31838.6-2021. The test results are shown in Table 2.

[0188] Table 2

[0189]

[0190]

[0191] By comparing Examples 1-3 with Comparative Example 1, it can be seen that the average particle size of the alumina powder is relatively fine, which will reduce the density of the alumina ceramic structural component and increase the dielectric loss value.

[0192] By comparing Examples 1-3 and Comparative Example 2, it can be seen that when the amount of lubricant and granulation powder surface modifier is low, the density of the alumina ceramic structural component will be reduced and the dielectric loss value will be increased.

[0193] By comparing Examples 1-3 and Comparative Example 3, it can be seen that: the cold isostatic pressing pressure is too low and the sintering temperature is too high, which will reduce the density of the alumina ceramic structural parts and increase the dielectric loss value.

[0194] By comparing Examples 1-3 and Comparative Example 4, it can be seen that when the amount of lubricant and granulation powder surface modifier is high, the density of the alumina ceramic structural component will be reduced and the dielectric loss value will be increased.

[0195] By comparing Examples 1-3 and Comparative Example 5, it can be seen that when the amount of dispersant used is high and the amount of granulating powder surface modifier used is low, the density of the alumina ceramic structural component will be reduced and the dielectric loss value will be increased.

[0196] By comparing Examples 1-3 and Comparative Example 6, it can be seen that when the amount of sintering aid is too high and the sintering temperature is too low, the density of the alumina ceramic structural component will be reduced and the dielectric loss value will be increased.

[0197] By comparing Examples 1-3 and Comparative Example 7, it can be seen that when the amount of sintering aid is too low and the sintering temperature is too high, the density of the alumina ceramic structural component will be reduced and the dielectric loss value will be increased.

Claims

1. A low dielectric loss alumina ceramic structural component, characterized in that: The preparation raw materials include: alumina powder, sintering aid, dispersant, adhesive, lubricant, granulation powder surface modifier, defoamer and plasticizer.

2. The low dielectric loss alumina ceramic structural component according to claim 1, characterized in that: The raw materials for preparing the alumina ceramic structural parts include, by weight: 100 parts of alumina powder, 0.1-0.3 parts of sintering aid, 2-4 parts of dispersant, 3-2 parts of adhesive, 0.8-2.5 parts of lubricant, 0.2-0.4 parts of granulating powder surface modifier, 0.01-0.05 parts of defoamer, and 0.5-1 parts of plasticizer.

3. The low dielectric loss alumina ceramic structural component according to claim 1, characterized in that: The purity of the aluminum oxide powder is greater than 99.99wt%, and the average particle size is less than 1.5μm.

4. The low dielectric loss alumina ceramic structural component according to claim 1, characterized in that: The sintering aid is a magnesium source compound, and the magnesium source compound includes one or more of magnesium oxide, magnesium hydroxide, magnesium nitrate hexahydrate, and magnesium carbonate.

5. The low dielectric loss alumina ceramic structural component according to claim 4, characterized in that: The magnesium content in the magnesium source compound is 500-1200ppm based on the mass of the alumina powder.

6. The low dielectric loss alumina ceramic structural component according to any one of claims 1 to 5, characterized in that: The dispersant includes: one or more of sorbitan monooleate, ammonium polyacrylate, ammonium polycarboxylate, polyvinyl pyrrolidone, and ethylenediaminetetraacetic acid ammonium salt.

7. The low dielectric loss alumina ceramic structural component according to claim 1, characterized in that: The adhesive comprises: one or more of PVA, methyl methacrylate and maltodextrin.

8. The low dielectric loss alumina ceramic structural component according to claim 1, characterized in that: The lubricant includes one or more of stearic acid, oxidized polyethylene wax emulsion and triglyceride.

9. The low dielectric loss alumina ceramic structural component according to claim 1, characterized in that: The granulating powder surface modifier comprises one or more of cationic polyacrylamide, hydroxypropyl methylcellulose and ethyl cellulose.

10. A method for preparing a low dielectric loss alumina ceramic structural component according to any one of claims 1 to 9, characterized in that: include: S1. Add sintering aid, dispersant, adhesive, lubricant, granulation powder surface modifier, defoamer and plasticizer into the ball mill containing grinding media and mix them evenly; S2, adding alumina powder, ball milling for 8-24 hours, and then centrifugal spray granulation to obtain granulated powder; S3. Fill the mold with granulated powder, seal it, and cold isostatically press it at 180-220 MPa for 10-20 min to obtain a green body. Then, air sinter it at 1590-1640°C for 2-4 h to obtain the green body.

Citation Information

Patent Citations

  • Low dielectric loss alumina ceramic material

    CN106938920A

  • Submicrometer-structured ultrathin alumina ceramic substrate and preparation method

    CN109160809A